The Evolution of Romanian SMEs Performance – Multi-year Analysis between 2011 and 2015 - Ștefan-Florin CORCODEL (Revista de Management Comparat International)
Evaluating an indicator has always been the first step needed in order to assure the improvement of that certain indicator. Having this principle in mind, the current paper aims to analyse the evolution of performance within Romanian small and medium-sized enterprises, between 2011 and 2015. In order to assure a relevant and correct evaluation, the analysis was carried taking into account multiple key performance indicators: number of employees, volume of receivables, volume of provider liabilities, volume of sales and amount of profit. The most significant result of the analysis refers to a general improvement of the performance of Romanian SMEs in the five years of analysis, with a peak of performance in 2015. The synergy of positive results registered in the multiple areas that were analysed resulted in a positive evolution of the most important KPI of an economic organization: its profit.